2006
DOI: 10.1080/0360123060096419
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Repellency of Hot Pepper Extracts to Spider Mite, Tetranychus urticae Koch

Abstract: Increasing concern about persistence and environmental impact of synthetic pesticide residues require development of biodegradable and environmentally safe alternatives. The potential of using fruit extracts of hot pepper as alternatives to synthetic acaricides for controlling the two-spotted spider mite, Tetranychus urticae Koch, is explored in this study. Twenty-four Capsicum accessions (Solanaceae) were screened for their toxicity and repellency to the spider mites. Crude extracts from fruits of C. chinense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 19 publications
0
26
0
1
Order By: Relevance
“…Although there are no differences among morphologically leaf features of these cultivars in terms of physical barriers such as trichome density, cvs AHCRI-Çarliston, AHCRI-Kandil Dolma and AHCRI-Yağlık are more susceptible for T. urticae. This difference among the cultivars is likely to be related to concentrations of phenolic compounds and alkaloids (i.e., capsaicin) in these cultivars (Keleş, 2007;Bozokalfa, 2009;Li et al, 2011Li et al, , 2015 and/or possibly the lack of nutrients needed for fecundity of the mite (van den Boom et al, 2004;Antonious et al, 2006). Although the quantity of capsaicin in the hot cultivars (about 10-15 fold compared with sweet ones) is well known (Bozokalfa, 2009), the phenolic content of the pepper cultivars has not been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no differences among morphologically leaf features of these cultivars in terms of physical barriers such as trichome density, cvs AHCRI-Çarliston, AHCRI-Kandil Dolma and AHCRI-Yağlık are more susceptible for T. urticae. This difference among the cultivars is likely to be related to concentrations of phenolic compounds and alkaloids (i.e., capsaicin) in these cultivars (Keleş, 2007;Bozokalfa, 2009;Li et al, 2011Li et al, , 2015 and/or possibly the lack of nutrients needed for fecundity of the mite (van den Boom et al, 2004;Antonious et al, 2006). Although the quantity of capsaicin in the hot cultivars (about 10-15 fold compared with sweet ones) is well known (Bozokalfa, 2009), the phenolic content of the pepper cultivars has not been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Embora a maior taxa de mortalidade tenha ocorrido no período de 48-72h de exposição dos ácaros ao extrato, não houve diferença significativa entre os tratamentos. O efeito letal sobre os ácaros podem diferir entre experimentos, uma vez que a quantidade e concentração das substâncias antagônicas podem variar, em relação à espécie de Capsicum (Antonius, 2006), como também pelas metodologias de extração, grau de maturação do fruto, e pelas condições ambientais a que a planta foi submetida durante o seu crescimento, tais como temperatura e luminosidade (Iorizzi et al, 2000). Mas de modo geral concentrações acima de 8% do extrato aquoso, tornariam difícil sua utilização em aplicações no campo, com o objetivo de rápida redução da população de ácaros fitófagos.…”
Section: Resultsunclassified
“…Exposure-interval-dependent variation in the percent efficacy of all tested plant extracts against mites may be attributable to the longer exposure of mites to treated grains, which increases the probability of contact of mites with the treated grains and, ultimately, with the toxic compound(s) of plant extracts. EC 50 Mansour et al 1986Mansour et al , 1997Sundaram and Sloane 1995;Dahroug et al 2000;Guirado et al 2001;Jazzar et al 2003;Mateeva et al 2003;Mansor et al 2004;Thevan et al 2005;Antonious et al 2006;Chiffelle et al 2009;Kumral et al 2010;Abbasipour et al 2011;Yanar et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These results conform to those of Kumral et al (2010), who reported mortality between 29% and 98% in females exposed to a leaf extract of D. stramonium after an exposure period of 48 h. Leaf extracts of D. stramonium are reported to be highly toxic against all life stages of different mites, including spider mites (Mateeva et al 2003) and the flat mite, Brevipalpus phoenicis (Geijskes) (Guirado et al 2001;Thevan et al 2005). Antonious et al (2006) and Kumral et al (2010) Dahroug et al (2000), who reported that a hexane extract of bitter apple seed (C. colocynthis) was the most effective against females of T. urticae and resulted in significant reductions in population density in the ranges of 74.42%-95.10% and 71.05%-95.55% a day after spraying with 0.6% and 5.0% bitter concentration extract, respectively. The greater population reduction at lower C. colocynthis concentrations (0.6%-5.0%) and shorter exposure intervals (1 day) in the study of Dahroug et al (2000) may be due to variations in experimental conditions or the extracting medium/chemical.…”
Section: Discussionmentioning
confidence: 99%